Efficiency of ProTaper Universal Retreatment, Reciproc Blue and XP-endo Shaper in the removal of a bioceramic-based root canal filling - Elif Çiftçioğlu; Rezan Sungur Güzel; Gözde Akbal Dinçer; Güneş Karakaya; Enver Sedat Küçükay (European Oral Research)
Purpose: This in vitro study aimed to assess the performance of ProTaper Universal Retreatment (PTUR), Reciproc Blue (RB), and XP-endo Shaper (XPS) system in the removal of bioceramic root canal filling. Materials and Methods: Forty-five human single-rooted mandibular premolars were prepared up to 30/.04 and filled with Endosequence BC sealer and BC points before being assigned into three groups (n=15). The root canal fillings were removed until reaching predetermined working length (WL) with PTUR in group 1, RB in group 2, and XPS in group 3. During the removal of the filling material, apically extruded debris was collected in preweighed Eppendorf tubes, and operation time was recorded with a digital chronometer. Reaching the WL and maintaining apical patency were evaluated separately. The data were statistically analyzed using Kruskal Wallis and Mann Whitney U tests. Results: The mean amount of extruded debris was highest in the PTUR group, although all instruments caused apical extrusion of debris. The mean time for reaching WL was longest for RB and shortest for XPS, with significant differences among the groups (p<0.05). Although the difference was not significant (p=0.799), in the PTUR group the WL was reached in 93.3% of the samples, which was higher than other groups (86.7%). Conclusion: All tested systems caused a certain amount of debris extrusion. XPS was associated with less extrusion while regaining more rapid access to the periapical area than PTUR and RB.